The Need For Kepping Hope Reflected In Mitch Albom s The First Phone Call From Heaven (2013) Sociological Approach - Sudamtoko, Hemix Gatut, Dr. M. Thoyibi, M.S (2017)
This research was to analysis the need for keeping hope in the novel of Mitch Albom's The First Phone Call From Heaven 2013 by using sociological approach. This objectives of the study is to identification the hope in the people. When the people always have a hope, he show characteristic optimism. Here the researcher used qualitative research to indentify hope in the characters. Primary data and secondary data are two type of data in this study. The primary data from the researcher is The First Phone Call From Heaven by Mitch Albom novels and translation novels in Indonesian language Telepon Pertama Dari Surga by Julanda Tantani. And the secondary data the researchers was taken from the iterature, research, thesis, dissertation, international journal, internet and any other source with can support this study. The technique of collecting data as follows: reading novel, Browsing to the internet, identifying, Taking important and Drawing conclusion and suggestion. The result shows the characters in the novel to showing characteristic of optimism such as, accepting past event, being grateful, being good listener, forgiving, healthy lifestyle, positive thinking, sharing experience, smiling, stop blaming, willing. The other result related sociology of literature that shows literary as manifestation situation of the author that influences the author of novel to write this used the need for keeping hope as reflection the author during his mother tending sick was suffering a stroke. We can conclude that required maintaining hope, in this research it can be seen from character figure in the phone, heaven and the god.